Pre-Service EFL Teachers’ Anxiety in Teaching English Speaking Skills - Fitriani, Indah; Rachmawati, Etika; Faridah, Didih (Journal of English Education Program (JEEP), 2025)
This study discusses pre-service EFL teachers’ anxiety in teaching English speaking skills focusing on the strategies to reduce the anxiety and how it affects the quality of teaching. The qualitative case study is conducted in a University in Ciamis involving 23 pre-service EFL teachers. Questionnaires were used to gather the data. The first result reveals that pre-service EFL teachers need to implement some strategies to motivate students and reduce anxiety in teaching English as a foreign language. Meanwhile, the second result shows that pre-service EFL teachers’ were mentally anxious related to all teaching English speaking skills activities, but for most of them, it did not really diminish their confidence while performing in front of class. Promoting learning activities without excessive pressure, emphasizing language importance, evaluating errors, and maintaining ethical conduct can reduce anxiety in teaching English speaking skills as pre-service teachers. For future researchers, the writer suggests they investigate the anxiety of pre-service EFL teachers assisted with psychologists to find a better solution.